2010
DOI: 10.1074/jbc.m109.058909
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the N-terminal Regulatory Domain of a Plant NADPH Oxidase and Its Functional Implications

Abstract: Plant NADPH oxidases (Rboh, for respiratory burst oxidase homolog) produce reactive oxygen species that are key regulators of various cellular events including plant innate immunity. Rbohs possess a highly conserved cytoplasmic N-terminal region containing two EF-hand motifs that regulate Rboh activity. Rice (Oryza sativa) RbohB (OsRbohB) is regulated by the direct binding of a small GTPase (Rac1) to this regulatory region as well as by Ca 2؉ binding to the EF-hands. Here, we present the atomic structure of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(128 citation statements)
references
References 45 publications
8
119
0
1
Order By: Relevance
“…Additionally, we found that the number of bleaching steps ranged from one to two, indicating that GFP-RbohD at the plasma membrane exists in multiple oligomeric forms, including monomers and dimers. This is consistent with previous crystallographic studies (Oda et al, 2010), which reported that the active conformation of OsRbohB is a dimer and that monomers interact via their terminal cytoplasmic domains. The dispersion of the diffusion coefficient distribution and the different oligomeric states suggest that GFP-RbohD is highly mobile and heterogeneously distributed at the plasma membrane.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, we found that the number of bleaching steps ranged from one to two, indicating that GFP-RbohD at the plasma membrane exists in multiple oligomeric forms, including monomers and dimers. This is consistent with previous crystallographic studies (Oda et al, 2010), which reported that the active conformation of OsRbohB is a dimer and that monomers interact via their terminal cytoplasmic domains. The dispersion of the diffusion coefficient distribution and the different oligomeric states suggest that GFP-RbohD is highly mobile and heterogeneously distributed at the plasma membrane.…”
Section: Discussionsupporting
confidence: 82%
“…OsRbohB acts downstream of Os-Rac1 through a direct interaction of its N-terminal EF-hand motif with GTP-bound Os-Rac1 (Wong et al, 2007;Oda et al, 2010;Kosami et al, 2014), and, as shown in this study, Os-RbohH is also involved in Rac1-mediated immunity. Proteome analyses have identified Rbohs in DRMs of tobacco, Arabidopsis and rice (Morel et al, 2006;Kierszniowska et al, 2009;Fujiwara et al, 2009), and ROS production by Rbohs in pollen tube tips is dependent on PM microdomains in Picea meyeri (Liu et al, 2009).…”
Section: Role Of Pm Microdomains In the Rac1-rbohb/h-mediated Mti Patmentioning
confidence: 81%
“…Os-Rac1 interacts with the N-terminal EF-hand motif of Os-RbohB, leading to an increase in ROS production (Wong et al, 2007;Oda et al, 2010;Kosami et al, 2014). To understand whether PM microdomains are necessary for ROS production mediated by the Rac1-Rboh pathway, we measured ROS production in OsFAH1/2-KD using the L-012 reagent.…”
Section: Os-fahs Are Involved In Ros Production After Chitin Treatmentmentioning
confidence: 99%
“…В результате происходит образование активно-го димера, приводящее к усилению генерации АФК [20]. Позднее на примере одной из форм мембраносвязанной субъединицы NADPH оксидазы риса (OsRBOHB) было показано на-личие в Nтерминальной области EFрук, ука-зывающих на формирование димера с участием кальция [43]. Таким образом, повышение актив-ности NADPHоксидазы с участием кальция, повидимому, связано не только с активацией им протеинкиназы, но и с прямым взаимодействи-ем Ca 2+ с каталитической субъединицей.…”
Section: +unclassified